A CONCEPTUALIZATION OF PROBLEMATIC SOCIAL MEDIA USE AMONG ADOLESCENTS - Nur Haffiza Rahaman; Liley Afzani Saidi; Wan Su Emi Yusnita Wan Yusof; Siti Nurhafizah Saleeza Ramlee; Rayyan Cheong Tian Ming Abdullah (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Social media have a significant impact on the everyday lives of its users in the digital age. This research paper provides a comprehensive overview of the problematic use of social media among adolescents, a group of users experiencing important physical, cognitive, and psychosocial changes. With 90% of adolescents aged 13-17 using social media, this paper highlights the negative consequences of excessive and compulsive use of these platforms, known as problematic social media use. Research studies have shown a direct correlation between problematic social media use and adverse outcomes such as anxiety, depression, low self-esteem, and social isolation. Illustrative cases are provided in the paper, showcasing adolescents who have faced severe mental health challenges and, tragically, resorted to suicide as a result of their social media addiction. This paper aims to identify and categorize the risk factors of problematic social media use into individual and social factors. Research data underscores the susceptibility of adolescents, especially females, to social media addiction and its consequent mental health well-being. Consequently, this paper proposes interventions and prevention strategies to mitigate the adverse consequences of excessive social media usage, including educational programs and parental guidance from international perspectives on problematic social media use.